Institutional economics: A sketch of economic growth policy - Walter Buhr (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2018)
In the postwar period until today the call for more intensive economic growth, again and again, enjoyed a substantial popularity in the world of politics, in particular with reference to possible current solutions of given economic problems. Here growth considerations and decisions in the past concentrating on some few years will be critically evaluated and found to be inadequate. Since economic growth is a long-term phenomenon, pertaining institutional and organizational precautions for formulating policies must be taken that will embody the preconditions of growth, the infrastructure of the market economy. In this context a proposal will be made on the basis of a wellknown constitutional model.
Keywords: D78; H54; J10; J24; K10; O10; P11; 330; Economic growth; growth policy; growth theory; capacity effects; endangering the future; EU-integration; biology; infrastructure; constitutional model (von Hayek); assignment ofinfrastructural measures